Can artificial intelligence surpass human intelligence: technical and philosophical perspectives? - Polina Taran; Viktoria Shved; Denisenko Nataliia (Закарпатський угорський інститут імені Ференца Ракоці II, 2024)
Abstract. In the modern world, the rapid development of artificial intelligence causes numerous discussions about its potential and capabilities. AI already performs tasks that were previously considered purely human, such as analyzing large amounts of information, recognizing speech, and making decisions based on data. In medicine, AI is used to improve diagnostics. For example, systems based on deep learning can analyze medical images such as X-rays and MRIs with high accuracy. This allows diseases such as cancer to be detected in the early stages, which significantly increases the chances of successful treatment. Autonomous vehicles, such as self-driving cars, use AI to process data from sensors and cameras, allowing them to navigate the road, avoid obstacles, and make real-time decisions. This can reduce the number of traffic accidents and improve road safety. In finance, AI helps detect fraudulent transactions, predict market trends, and automate trading. Associated with virtual assistants such as Siri or Google Assistant, speech recognition systems use AI to convert spoken speech into text. This allows users to interact with devices using voice commands, facilitating access to information and device management. Chatbots and virtual assistants, like those used in online stores or customer support, help automate the processing of inquiries and provide quick answers to common questions. This reduces the burden on human operators and improves the quality of customer service. On online shopping platforms such as Rozetka or Prom, AI analyzes purchase and browsing history to create personalized product recommendations. This helps users find the products they are interested in and increases sales efficiency for companies.
Keywords: Artificial intelligence; human intelligence